Can I keep him? - Kellogg, Steven (New York : Dial Press, 1971)
Mother objects to every pet Arnold asks to keep except one--a person.
Keywords: Pets -- Fiction; Pets -- Fiction; Integrated Ed -- Language arts -- Early elementary; Pets -- Fiction